Effects of Silica Fume and Steel Fibers on Some Mechanical Properties of High-Strength Fiber-Reinforced Concrete - Eren, Özgür; Marar, Khaled; Çelik, Tahir (ASTM International, 1999)
There are many test methods to measure the impact resistance of fiber-reinforced concrete that are complicated, time consuming, and expensive. A practical test method has been developed to measure the impact resistance of high-strength fiber-reinforced concrete (HSFRC). The equipment developed can also be used for testing aggregate impact values by simply changing the base plate of the machine. A machine was developed to measure the surface abrasion resistance of HSFRC. Testing fiber-reinforced concrete for surface abrasion resistance was found to be extremely difficult if realistic and practical results were desired. In this study the influence of silica fume on the properties of HSFRC was investigated by using silica fume at two different percentages and with three different hooked-end fibers, namely, 30/0.50, 60/0.80, and 50/0.60 length/diameter (mm/mm). Fibers were added to concrete in three different percentages of 0.5, 1.0, and 2.0% by volume of concrete. The results show that including fibers in high-strength concrete improves impact resistance, surface abrasion, and splitting tensile strength.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1520/JTE12166) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: high-strength concrete; fiber reinforced concrete; impact resistance; abrasion resistance